Natural dyeing of cotton fabrics with licorice extract: the role of mordants in enhancing color fastness and protection from ultraviolet rays - Sharouf, Hoda; Salamon, Reem (Al-Nahrain Journal for Engineering Sciences, 2026)
The usage of non-toxic, eco-friendly natural dyes on textiles has achieved notable attention due to increased environmental attention about avoiding hazardous synthetic dyes. This has prompted a return to natural dyes and the search for new sources, especially locally available ones like licorice. In this study, Glycyrrhiza glabra extract (70 g/l), prepared using ultrasound assistance, was used to dye cotton samples. The natural dyeing process employed a simultaneous mordanting method with zinc chloride and alum as mordants, in many concentrations (1, 3, 5, 7 and 10 g/l). The color fastness of the dyed samples was evaluated using a scanner and ImageJ. The fastness of the dyed fabrics was tested against washing and rubbing, and samples with licorice extract showed excellent stability. A tear strength test was also conducted to assess the impact of licorice extract dyeing on the mechanical properties of the samples. It was observed that dyeing with licorice reduced the tear strength, but increasing the concentration of mordants improved the resistance to tearing, making the mordanted samples stronger than the mordanted ones.